A composite ion exchange membrane and preparation method thereof
By performing ultraviolet radiation in the ion exchange membrane, adding modified silicon dioxide, and constructing ZIF-8 nanoscope, the problem of low mechanical strength and short service life of existing ion switching membranes is solved. Poisability resistance and anti -pollution ability.
Patent Information
- Application Number
- CN202311571105.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-11-23
AI Technical Summary
The existing ion exchange membranes have problems such as low mechanical strength, poor dimensional stability, poor chemical stability, inability to acid and alkali resistance and poor pollution resistance, resulting in short service life.
By connecting the polyfront fluoride for ultraviolet sprains to connect the sodium lycrazine sulfonate, add the modified silicon dioxide and construct the ZIF-8 nanowe on the surface of the membrane to form a composite ion exchange membrane.
It improves the mechanical strength, acid and alkali resistance, anti-pollution ability and service life of the ion exchange membrane, and enhances its economy and recyclability in industrial applications.
Smart Images

Figure BDA0004565531580000111 
Figure BDA0004565531580000112
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation materials, and in particular relates to a composite ion exchange membrane and a preparation method thereof. Background Art
[0002] Membrane separation technology has become an important part of production and life, including many membrane-based separation and purification processes. In addition, the application of membrane separation technology in high-tech fields (such as biotechnology, nanotechnology, and membrane-based energy devices) is also growing. Due to the low energy consumption of membrane technology during operation and the easy scale-up of module design, membrane-based processes are economically feasible, and the application research of membrane technology and the development of new membrane materials are becoming more and more competitive. At present, there are various types of separation membranes used for reverse osmosis, nanofiltration, ultrafiltration, microfiltration, electrodialysis, fuel cells, etc., among which ion exchange membrane is one of the most advanced separation membranes.
[0003] At present, the country attaches great importance to energy conservation and environmental protection issues, especially the current requirements for zero discharge of high-salt wastewater and zero discharge in industrial production processes are getting higher and higher. Therefore, ion exchange membranes with simple process, energy saving and strong anti-pollution ability have attracted widespread attention and have developed into the main direction of future research. The preparation method of ion exchange membranes has always been the focus of research. The research on the preparation process of ion exchange membranes has great economic value. The application of ion exchange membranes in water treatment and electrodialysis can greatly save energy and protect the environment.
[0004] Electrodialysis utilizes the selective permeability of ion exchange membranes to anions and cations. Under the action of the DC electric field at both ends, the anions and cations in the feed solution are directed to move, thereby achieving the purpose of separation, purification and concentration of electrolyte solutions. Therefore, ion exchange membranes are the main core components of the electrodialysis process. Ion exchange membranes are usually composed of hydrophobic substrates, fixed functional groups and active ion exchange groups. They are a kind of reticular polymer functional membrane with selective permeability. According to the fixed charge properties in the membrane structure, they are divided into cation exchange membranes and anion exchange membranes. Among them, cation exchange membranes are membranes that have selective effects on cations, usually sulfonic acid type, with selective permeability. The performance of cation exchange membranes largely determines the effect of the electrodialysis process. The technical methods for improving the performance of cation exchange membranes mainly include doping modification and surface modification, which are also hot research topics in recent years.
[0005] Chinese patent application No. 201711491825.8 discloses a cation exchange membrane and a method for preparing the same. The membrane has a semi-interpenetrating network structure, a microporous membrane as a supporting material, and a functional polymer filled in the membrane pores. The functional polymer contains a structure formed by polymerization of allyloxybenzenesulfonic acid pyridinium salt or alkyl allyloxybenzenesulfonic acid pyridinium salt. The method for preparing the membrane comprises the following steps: (1) a monomer preparation step, wherein sodium p-hydroxybenzenesulfonate is reacted with 3-halogenated propene or 3-halogenated 2-alkyl propene, and the obtained product is further reacted with pyridine hydrochloride to obtain a monomer solution; (2) a membrane forming step, wherein the monomer solution is mixed with a cross-linking agent, an initiator and a comonomer to form a membrane-forming liquid, and the membrane-forming liquid is filled into the pores of the microporous membrane supporting material, and the temperature is raised to cause a polymerization reaction to obtain a cation exchange membrane. The defects of this invention are poor recycling performance and a short service life of the cation exchange membrane.
[0006] At present, ion exchange membranes generally have problems: low mechanical strength, poor dimensional stability, poor chemical stability, acid and alkali resistance, poor anti-pollution ability and other shortcomings. Therefore, providing a composite cation exchange membrane that is resistant to organic solvents, has good mechanical properties and good durability has become an urgent development need. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a composite ion exchange membrane and a preparation method thereof, wherein the composite ion exchange membrane has high selectivity and service life, and also has good mechanical strength, acid and alkali resistance and pollution resistance, is convenient for industrial promotion, and improves the economic efficiency of industrial production.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a composite ion exchange membrane comprises the following steps:
[0010] S1, adding polyvinylidene fluoride to a solvent, stirring to dissolve, then adding benzophenone and sodium styrene sulfonate, and irradiating with ultraviolet light to obtain a sulfonated polyvinylidene fluoride solution;
[0011] S2, adding silicon dioxide to toluene, then adding isocyanate propyl triethoxysilane, stirring to react, adding N-(3-aminopropyl) imidazole and stannous octoate after the reaction is completed, and reacting at a constant temperature under nitrogen conditions, filtering, washing, and drying after the reaction is completed to obtain modified silicon dioxide;
[0012] S3, adding the modified silicon dioxide and dibutyl phthalate in step S2 to the polyvinylidene fluoride solution in step S1, stirring and dispersing them evenly to obtain a casting solution, and then performing ultrasonic degassing, film-forming by scraping, vacuum drying and film stripping to obtain a base film;
[0013] S4, adding the base film in step S3 to a zinc nitrate-hexamethylenetetramine aqueous solution for heating reaction, adding to a dimethylimidazole solution for etching reaction after the reaction is completed, washing and drying after the reaction is completed, so as to obtain the composite ion exchange membrane.
[0014] Preferably, the solvent in step S1 is one or two of N,N-dimethylformamide and dimethylacetamide; the mass ratio of the polyvinylidene fluoride, solvent, benzophenone and sodium styrene sulfonate is 20-30:100:0.5-1:15-20.
[0015] Preferably, the intensity of the ultraviolet radiation in step S1 is 10-15 mW / cm 2 , time is 4-8min.
[0016] Preferably, the mass ratio of silicon dioxide, isocyanatepropyltriethoxysilane, N-(3-aminopropyl)imidazole and stannous octoate in step S2 is 50:10-20:5-10:0.3-0.6.
[0017] Preferably, the stirring reaction in step S2 is carried out at a temperature of 60-70°C for 1-2 hours; and the isothermal reaction is carried out at a temperature of 75-85°C for 5-8 hours.
[0018] Preferably, in step S3, the amount of modified silicon dioxide added is 10-15% of the polyvinylidene fluoride; and the amount of dibutyl phthalate added is 5-10% of the polyvinylidene fluoride.
[0019] Preferably, in step S4, the concentration of zinc nitrate in the zinc nitrate-hexamethylenetetramine aqueous solution is 0.1-0.5 mol / L, the concentration of hexamethylenetetramine is 0.1-0.5 mol / L, the temperature of the heating reaction is 80-90° C., and the time is 4-5 h.
[0020] Preferably, the mass fraction of the dimethylimidazole aqueous solution in step S4 is 10-15%; the temperature of the in-situ etching is 20-30° C., and the time is 8-13 h.
[0021] The present invention also protects a composite ion exchange membrane prepared by the method.
[0022] The present invention also protects the application of the composite ion exchange membrane in the fields of water electrolysis, electrodialysis and membrane separation.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The composite ion exchange membrane provided by the present invention comprises the following steps: firstly, polyvinylidene fluoride is irradiated with ultraviolet light to connect with sodium styrene sulfonate, so that sulfonic acid groups are introduced into the polyvinylidene fluoride to prepare cationic sulfonated polyvinylidene fluoride; then, modified SiO2 is added by doping to prepare a base membrane; the addition of modified SiO2 increases the surface roughness of the membrane, thereby increasing the contact area between ions and the membrane, improving the exchange capacity, mechanical properties and stability of the ion exchange membrane; then, the base membrane is placed in a zinc nitrate-hexamethylenetetramine aqueous solution to epitaxially grow zinc oxide nanorods on the surface of the base membrane; finally, the base membrane is reacted with dimethylimidazole to grow ZIF-8 nanorods on the in-situ skeleton; and ZIF-8 nanorods are constructed on the surface of the polyvinylidene fluoride cation exchange membrane to form micro-nano roughness and low surface energy on the membrane surface. Due to the high stability and acid and alkali resistance of ZIF-8, the ion exchange membrane has good stability and excellent recyclability, thereby improving the service life of the ion exchange membrane.
[0025] (2) The composite ion exchange membrane provided by the present invention comprises modified silica, wherein the silica is first reacted with isocyanatepropyltriethoxysilane to introduce isocyanate onto the surface of the silica, and then reacted with N-(3-aminopropyl)imidazole to introduce imidazole groups onto the surface of the silica. The hygroscopic properties of the imidazole groups provide sufficient water molecules for the channels of the ion exchange membrane, thereby forming a wider and continuous nanochannel configuration. The Lewis basic N atoms in the imidazole group structure can bind to protons, thereby serving as proton transfer sites, thereby increasing the exchange capacity of the ion exchange membrane. In addition, The hydrogen bond interaction between water molecules and the two nitrogen atoms on the imidazole ring promotes the conduction of protons and improves the selective permeability of the composite ion exchange membrane to cations; at the same time, the N atom in the introduced imidazole group has high electronegativity and a compact molecular structure, which is easy to form intermolecular hydrogen bonds, thereby improving the mechanical strength of the composite ion exchange membrane; and the imidazole group in the modified silica contains a long-chain silane bond, which has a large steric hindrance and forms a large cationic group after combining with a high-valent cation, thereby playing a good barrier role for the high-valent cations and improving the selective permeability of the separation membrane to cations of different valences. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The polyvinylidene fluoride was purchased from Dongguan Jingke Polymer Co., Ltd., with the brand name of French Arkema HSV900 and a molecular weight of 900,000; the silicon dioxide was purchased from Qinghe Chaotai Metal Materials Co., Ltd., with a particle size of 500 nm.
[0028] Example 1
[0029] A method for preparing a composite ion exchange membrane comprises the following steps:
[0030] S1. Add 25g of polyvinylidene fluoride to 100g of dimethylacetamide and stir to dissolve. Then add 0.8g of benzophenone and 18g of sodium styrene sulfonate. 2 The irradiation was carried out for 6 minutes, and a sulfonated polyvinylidene fluoride solution was obtained after the irradiation was completed;
[0031] S2, add 50g of silica to 500mL of toluene, then add 15g of isocyanatepropyltriethoxysilane, stir and react at 65°C for 1.5h, add 8g of N-(3-aminopropyl)imidazole and 0.5g of stannous octoate after the reaction is completed, and carry out constant temperature reaction under nitrogen, the reaction temperature is 80°C, the time is 7h, and after the reaction is completed, filter, wash and dry to obtain modified silica;
[0032] S3, adding 3g of modified silicon dioxide and 2g of dibutyl phthalate in step S2 to the polyvinylidene fluoride solution in step S1, stirring and dispersing them evenly to obtain a casting solution, subjecting the casting solution to ultrasonic degassing for 15min, then pouring the casting solution onto a smooth glass plate and scraping it into a film, then placing it in a vacuum drying oven and drying it at 85°C for 22h, then taking the film out of the drying oven and cooling it to room temperature in air to obtain a base film;
[0033] S4. Add the basement membrane in step S3 into a zinc nitrate-hexamethylenetetramine aqueous solution, wherein the concentration of zinc nitrate is 0.3 mol / L and the concentration of hexamethylenetetramine is 0.3 mol / L, and react at 85°C for 4.5 hours. After the reaction is completed, remove the basement membrane, add it into a 12% by mass dimethylimidazole aqueous solution, and react at 25°C for 10 hours. After the reaction is completed, wash and dry to obtain the composite ion exchange membrane.
[0034] Example 2
[0035] A method for preparing a composite ion exchange membrane comprises the following steps:
[0036] S1. Add 25g of polyvinylidene fluoride to 100g of N,N-dimethylformamide and stir to dissolve. Then add 0.7g of benzophenone and 18g of sodium styrene sulfonate. 2The irradiation was carried out for 6 minutes, and a sulfonated polyvinylidene fluoride solution was obtained after the irradiation was completed;
[0037] S2, add 50g of silica to 500mL of toluene, then add 15g of isocyanatepropyltriethoxysilane, stir and react at 65°C for 1.5h, add 7g of N-(3-aminopropyl)imidazole and 0.4g of stannous octoate after the reaction is completed, and carry out constant temperature reaction under nitrogen, the reaction temperature is 80°C, the time is 6h, and after the reaction is completed, filter, wash and dry to obtain modified silica;
[0038] S3, adding 3g of modified silicon dioxide and 2g of dibutyl phthalate in step S2 to the polyvinylidene fluoride solution in step S1, stirring and dispersing them evenly to obtain a casting solution, subjecting the casting solution to ultrasonic degassing for 15min, then pouring the casting solution onto a smooth glass plate and scraping it into a film, then placing it in a vacuum drying oven and drying it at 85°C for 24h, then taking the film out of the drying oven and cooling it to room temperature in air to obtain a base film;
[0039] S4. Add the basement membrane in step S3 into a zinc nitrate-hexamethylenetetramine aqueous solution, wherein the concentration of zinc nitrate is 0.4 mol / L, and the concentration of hexamethylenetetramine is 0.4 mol / L, and react at 85°C for 4.5 hours. After the reaction is completed, remove the basement membrane, add it into a 12% by mass dimethylimidazole aqueous solution, and react at 25°C for 11 hours. After the reaction is completed, wash and dry to obtain the composite ion exchange membrane.
[0040] Example 3
[0041] A method for preparing a composite ion exchange membrane comprises the following steps:
[0042] S1. Add 20g of polyvinylidene fluoride to 100g of dimethylacetamide and stir to dissolve. Then add 0.5g of benzophenone and 15g of sodium styrene sulfonate. 2 Irradiate for 8 minutes, and obtain a sulfonated polyvinylidene fluoride solution after the irradiation is completed;
[0043] S2, add 50g of silica to 500mL of toluene, then add 10g of isocyanatepropyltriethoxysilane, stir and react at 60°C for 2h, add 5g of N-(3-aminopropyl)imidazole and 0.3g of stannous octoate after the reaction is completed, and carry out constant temperature reaction under nitrogen, the reaction temperature is 75°C, the time is 8h, and after the reaction is completed, filter, wash and dry to obtain modified silica;
[0044] S3, adding 2g of modified silicon dioxide and 1g of dibutyl phthalate in step S2 to the polyvinylidene fluoride solution in step S1, stirring and dispersing them evenly to obtain a casting solution, subjecting the casting solution to ultrasonic degassing for 10min, then pouring the casting solution onto a smooth glass plate and scraping it into a film, then placing it in a vacuum drying oven and drying it at 80°C for 24h, then taking the film out of the drying oven and cooling it to room temperature in air to obtain a base film;
[0045] S4. Add the basement membrane in step S3 into a zinc nitrate-hexamethylenetetramine aqueous solution, wherein the concentration of zinc nitrate is 0.3 mol / L, and the concentration of hexamethylenetetramine is 0.3 mol / L, and react at 80°C for 5 hours. After the reaction is completed, remove the basement membrane, add it into a 10% by mass dimethylimidazole aqueous solution, and react at 20°C for 13 hours. After the reaction is completed, wash and dry to obtain the composite ion exchange membrane.
[0046] Example 4
[0047] A method for preparing a composite ion exchange membrane comprises the following steps:
[0048] S1. Add 30g of polyvinylidene fluoride to 100g of N,N-dimethylformamide and dimethylacetamide, stir and dissolve, then add 1g of benzophenone and 20g of sodium styrene sulfonate, and place under ultraviolet light at an intensity of 15mW / cm 2 Irradiate for 4 min, and obtain a sulfonated polyvinylidene fluoride solution after the irradiation is completed;
[0049] S2, add 50g of silica to 500mL of toluene, then add 20g of isocyanatepropyltriethoxysilane, stir and react at 70°C for 1h, add 10g of N-(3-aminopropyl)imidazole and 0.6g of stannous octoate after the reaction is completed, and carry out constant temperature reaction under nitrogen, the reaction temperature is 85°C, the time is 5h, and after the reaction is completed, filter, wash and dry to obtain modified silica;
[0050] S3, adding 4.5g of modified silicon dioxide and 3g of dibutyl phthalate in step S2 to the polyvinylidene fluoride solution in step S1, stirring and dispersing them evenly to obtain a casting solution, subjecting the casting solution to ultrasonic degassing for 20min, then pouring the casting solution on a smooth glass plate and scraping it into a film, then placing it in a vacuum drying oven, drying it at 90°C for 20h, then taking the film out of the drying oven, and cooling it to room temperature in air to obtain a base film;
[0051] S4. Add the basement membrane in step S3 into a zinc nitrate-hexamethylenetetramine aqueous solution, wherein the concentration of zinc nitrate is 0.3 mol / L, and the concentration of hexamethylenetetramine is 0.3 mol / L, and react at 90°C for 4 hours. After the reaction is completed, remove the basement membrane, add it into a 15% by mass dimethylimidazole aqueous solution, and react at 30°C for 8 hours. After the reaction is completed, wash and dry to obtain the composite ion exchange membrane.
[0052] Comparative Example 1
[0053] A method for preparing a composite ion exchange membrane comprises the following steps:
[0054] S1. Add 25g of polyvinylidene fluoride to 100g of dimethylacetamide and stir to dissolve. Then add 0.8g of benzophenone and 18g of sodium styrene sulfonate. 2 The irradiation was carried out for 6 minutes, and a sulfonated polyvinylidene fluoride solution was obtained after the irradiation was completed;
[0055] S2, adding 3g of silicon dioxide and 2g of dibutyl phthalate to the polyvinylidene fluoride solution in step S1, stirring and dispersing them evenly to obtain a casting solution, subjecting the casting solution to ultrasonic degassing for 15min, then pouring the casting solution onto a smooth glass plate and scraping it into a film, then placing it in a vacuum drying oven and drying it at 85°C for 22h, then taking the film out of the drying oven and cooling it to room temperature in air to obtain a base film;
[0056] S3. Add the basement membrane in step S2 into a zinc nitrate-hexamethylenetetramine aqueous solution, wherein the concentration of zinc nitrate is 0.3 mol / L and the concentration of hexamethylenetetramine is 0.3 mol / L, and react at 85°C for 4.5 hours. After the reaction is completed, remove the basement membrane, add it into a 12% by mass dimethylimidazole aqueous solution, and react at 25°C for 10 hours. After the reaction is completed, wash and dry to obtain the composite ion exchange membrane.
[0057] Comparative Example 2
[0058] A method for preparing a composite ion exchange membrane comprises the following steps:
[0059] S1. Add 25g of polyvinylidene fluoride to 100g of dimethylacetamide and stir to dissolve. Then add 0.8g of benzophenone and 18g of sodium styrene sulfonate. 2 The irradiation was carried out for 6 minutes, and a sulfonated polyvinylidene fluoride solution was obtained after the irradiation was completed;
[0060] S2, add 50g of silica to 500mL of toluene, then add 15g of isocyanatepropyltriethoxysilane, stir and react at 65°C for 1.5h, add 8g of N-(3-aminopropyl)imidazole and 0.5g of stannous octoate after the reaction is completed, and carry out constant temperature reaction under nitrogen, the reaction temperature is 80°C, the time is 7h, and after the reaction is completed, filter, wash and dry to obtain modified silica;
[0061] S3. Add 3g of modified silicon dioxide and 2g of dibutyl phthalate in step S2 to the polyvinylidene fluoride solution in step S1, stir and disperse evenly to obtain a casting solution, perform ultrasonic degassing on the casting solution for 15 minutes, then pour the casting solution on a smooth glass plate and scrape it into a film, then put it into a vacuum drying oven and dry it at 85°C for 22 hours, then take the film out of the drying oven and cool it to room temperature in air to obtain the composite ion exchange membrane.
[0062] The composite ion exchange membranes prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, wherein the tensile strength and elongation at break were tested using an electronic universal material testing machine at a tensile speed of 5 mm / min, a sample size of 150×25 mm, and a test temperature of room temperature to test the tensile strength and elongation at break of the membrane material;
[0063] The exchange capacity test is as follows: ① Take a flat and intact composite ion exchange membrane, cut it into 4cm×4cm size, and soak it in 1mol / L HCl solution at room temperature for 24h to allow the solution to reach complete equilibrium. Take it out and wash the surface of the membrane with deionized water. At this time, the membrane is converted into H + ②H + The membrane was immersed in 2 mol / L NaCl solution for 24 h to remove the H + Displaced, the membrane is converted into Na + Type membrane, use deionized water to wash away the residual H + , collect the washing water and soaking solution. ③ Using phenolphthalein as an indicator, titrate the solution collected in ② with 0.1 mol / L NaOH solution, and record the volume of NaOH solution consumed. ④ Wash the membrane with deionized water and place it in a vacuum oven at 60°C to dry for 6 hours until constant weight, and record the mass of the dry membrane. The obtained ion exchange capacity is calculated as follows:
[0064]
[0065] Where, IEC——ion exchange capacity, mmol / L; C NaOH ——Concentration of NaOH solution, mol / L; V NaOH ——Volume of NaOH solution consumed, mL; m1——mass of dry film, g.
[0066] The migration number of ion exchange membrane indicates the total current fraction of counter ions passing through the membrane, which can be used to characterize the selective permeability of the membrane to ions of opposite charges. It can generally be calculated by measuring the membrane potential. The present invention uses a single-membrane dual-chamber simulated electrodialysis device to measure the membrane potential. First, the composite ion exchange membrane sample to be tested is immersed in a 0.15 mol / L NaCl solution for more than 12 hours to convert it into Na + The membrane is then fixed in the electrolytic cell, and the left and right chambers are respectively injected with 0.1mol / L NaCl solution and 0.2mol / L NaCl solution of equal liquid level. The membrane potential is measured by connecting a multimeter with a calomel electrode corresponding to the same NaCl concentration, and the solution temperature is measured. The cation migration number t of the membrane is calculated as follows + (%):
[0067]
[0068] Where, t + ——cation migration number of ion exchange membrane, %; E 测 ——Membrane potential value measured by multimeter, mV; E0——Theoretical potential value of NaCl standard solution obtained by looking up the table according to the solution temperature, mV.
[0069] Stability test: The composite ion exchange membrane was placed in 1 mol / L dilute hydrochloric acid and 10 mA / cm 2 The current density was energized for 3 h, and the composite ion exchange membrane was taken out. According to the test ion exchange membrane migration number (Na + ), characterize the stability of the composite cation exchange membrane.
[0070] The specific test results are shown in Table 1:
[0071] Table 1
[0072] Tensile strength / MPa Elongation at break / % Exchange capacity mmol / g <![CDATA[Transport number (Na + )]]> stability / % Example 1 53.7 73.9 3.31 98.42 95.54 Example 2 52.9 71.4 3.14 97.83 93.68 Example 3 50.3 68.5 3.05 96.21 94.57 Example 4 55.1 70.2 3.26 98.47 95.06 Comparative Example 1 46.5 58.3 2.27 92.16 89.24 Comparative Example 2 49.6 67.7 3.12 97.52 82.39
[0073] It can be seen from the above table that the composite ion exchange membrane prepared by the present invention has good mechanical properties and exchange capacity, and at the same time has a high selective permeability to Na+. After acid treatment, the ion exchange membrane also has good selective permeability, which enhances the durability and selectivity of the composite cation exchange membrane and has good application prospects.
[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a composite ion exchange membrane, characterized in that: The following steps are involved: S1, adding polyvinylidene fluoride to a solvent, stirring to dissolve, then adding benzophenone and sodium styrene sulfonate, and irradiating with ultraviolet light to obtain a sulfonated polyvinylidene fluoride solution; S2, adding silicon dioxide to toluene, then adding isocyanate propyl triethoxysilane, stirring to react, adding N-(3-aminopropyl) imidazole and stannous octoate after the reaction is completed, and reacting at a constant temperature under nitrogen conditions, filtering, washing, and drying after the reaction is completed to obtain modified silicon dioxide; S3, adding the modified silicon dioxide and dibutyl phthalate in step S2 to the polyvinylidene fluoride solution in step S1, stirring and dispersing them evenly to obtain a casting solution, and then performing ultrasonic degassing, film-forming by scraping, vacuum drying and film stripping to obtain a base film; S4, adding the base film in step S3 to a zinc nitrate-hexamethylenetetramine aqueous solution for heating reaction, adding to a dimethylimidazole solution for etching reaction after the reaction is completed, washing and drying after the reaction is completed, so as to obtain the composite ion exchange membrane.
2. The method according to claim 1, characterized in that In step S1, the solvent is one or two of N,N-dimethylformamide and dimethylacetamide; the mass ratio of the polyvinylidene fluoride, the solvent, benzophenone and sodium styrene sulfonate is 20-30:100:0.5-1:15-20.
3. The method according to claim 1, characterized in that The intensity of the ultraviolet radiation in step S1 is 10-15 mW / cm 2 , time is 4-8min.
4. The method according to claim 1, characterized in that: The mass ratio of silicon dioxide, isocyanatepropyltriethoxysilane, N-(3-aminopropyl)imidazole and stannous octoate in step S2 is 50:10-20:5-10:0.3-0.
6.
5. The method according to claim 1, characterized in that The stirring reaction in step S2 is carried out at a temperature of 60-70°C for 1-2 hours; the constant temperature reaction is carried out at a temperature of 75-85°C for 5-8 hours.
6. The method according to claim 1, characterized in that In step S3, the amount of modified silicon dioxide added is 10-15% of the polyvinylidene fluoride; the amount of dibutyl phthalate added is 5-10% of the polyvinylidene fluoride.
7. The method according to claim 1, characterized in that In step S4, the concentration of zinc nitrate in the zinc nitrate-hexamethylenetetramine aqueous solution is 0.1-0.5 mol / L, the concentration of hexamethylenetetramine is 0.1-0.5 mol / L, the temperature of the heating reaction is 80-90° C., and the time is 4-5 h.
8. The method according to claim 1, characterized in that The mass fraction of the dimethylimidazole solution in step S4 is 10-15%; the temperature of the etching reaction is 20-30° C., and the time is 8-13 hours.
9. A composite ion exchange membrane prepared by the method according to any one of claims 1 to 8.
10. Use of the composite ion exchange membrane according to claim 9 in the fields of water electrolysis, electrodialysis and membrane separation.
Citation Information
Patent Citations
Cation exchange membrane and preparation method thereof
CN108067102A
Method for preparing hybridized ion exchange membrane
CN106345324A
Modified nanometer composite membrane as well as preparation method and application thereof
CN109499397A